2015
DOI: 10.1080/14786419.2015.1086347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticoagulant activity of two algal polysaccharides

Abstract: Marine algae are important sources of phycocolloids like agar, carrageenans and alginates used in industrial applications. Algal polysaccharides have emerged as an important class of bioactive products showing interesting properties. The aim of our study was to evaluate the potential uses as anticoagulant drugs of algal sulphate polysaccharides extracted from Ulva fasciata (Chlorophyta) and Agardhiella subulata (Rhodophyta) collected in Ganzirri Lake (Cape Peloro Lagoon, north-eastern Sicily, Italy). Toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 10 publications
0
31
0
2
Order By: Relevance
“…Sulfated polysaccharides from algae have been acknowledged to bear diversified biological and pharmacological functions [ 22 , 60 , 61 , 62 ]. Moreover, the chemical composition and structural features of polysaccharides were confirmed to function as determinants of their bioactivities [ 17 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sulfated polysaccharides from algae have been acknowledged to bear diversified biological and pharmacological functions [ 22 , 60 , 61 , 62 ]. Moreover, the chemical composition and structural features of polysaccharides were confirmed to function as determinants of their bioactivities [ 17 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that algal polysaccharides exhibit antioxidant, [12] , anticancer [13] and anticoagulant activities. [14] However, their neuroprotective effect has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…). There is growing trend in the replacement of chemical drugs with herbal medicine and algal extracts, due to their potential health benefits with limited side effects (Peddie, Zou & Secombes ; Najafian & Babji ; Faggio, Morabito, Minicante, Piano, Pagano & Genovese ; Faggio, Pagano, Dottore, Genovese & Morabito ). Therefore, the study about immunostimulants, especially those of plant origin, which have antioxidant and immune property, has remarkably increased in recent years (Galina, Yin, Ardo & Jeney ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of immunostimulants in the aquaculture industry has been important in reducing antibiotics use and economic losses which occur as a result of disease (Citarasu 2010;Genovese, Faggio, Gugliandolo, Torre, Span o, Morabito & Maugeri 2012;Hoseinifar, Esteban, Cuesta & Sun 2015;Hoseinifar et al 2016). There is growing trend in the replacement of chemical drugs with herbal medicine and algal extracts, due to their potential health benefits with limited side effects (Peddie, Zou & Secombes 2002;Najafian & Babji 2012;Faggio, Morabito, Minicante, Piano, Pagano & Genovese 2015;Faggio, Pagano, Dottore, Genovese & Morabito 2015). Therefore, the study about immunostimulants, especially those of plant origin, which have antioxidant and immune property, has remarkably increased in recent years (Galina, Yin, Ardo & Jeney 2009).…”
Section: Introductionmentioning
confidence: 99%